Genetic interaction studies reveal superior performance of Rhizobium tropici CIAT899 on a range of diverse East African common bean (Phaseolus vulgaris L.) genotypes - Gunnabo, A.H.; Geurts, R.; Woldemeskel, Endalkachew; Degefu, T.; Giller, Kenneth E.; Heerwaarden, Joost van (American Society for Microbiology, 2019)
The existence of genotype-by-strain (G L × G R ) interaction has implications for the expected stability of performance of legume inoculants and could represent both challenges and opportunities for improvement of nitrogen fixation. We find that significant genotype-by-strain interaction exists in common bean ( Phaseolus vulgaris L.) but that the strength and direction of this interaction depends on the growing environment used to evaluate biomass. Strong genotype and strain main effects, combined with a lack of predictable patterns in G L × G R , suggests that at best individual bean genotypes and strains can be selected for superior additive performance. The observation that the screening environment may affect experimental outcome of G L × G R means that identified patterns should be corroborated under more realistic conditions.